Molecular Evolution of the Protease Region in Norovirus Genogroup II - Ozaki, Keita; Matsushima, Yuki; Nagasawa, Koo; Aso, Jumpei; Saraya, Takeshi; Yoshihara, Keisuke; Murakami, Koichi; Motoya, Takumi; Ryo, Akihide; Kuroda, Makoto; Katayama, Kazuhiko; Kimura, Hirokazu (Frontiers in Microbiology, 2020)
Noroviruses are a major cause of viral epidemic gastroenteritis in humans worldwide. The protease (Pro) encoded in open reading frame 1 (ORF1) is an essential enzyme for proteolysis of the viral polyprotein. Although there are some reports regarding the evolutionary analysis of norovirus GII-encoding genes, there are few reports focused on the Pro region. We analysed the molecular evolution of the Pro region of norovirus GII using bioinformatics approaches. A time-scaled phylogenetic tree of the Pro region constructed using a Bayesian Markov chain Monte Carlo method indicated that the common ancestor of GII diverged from GIV around 1680 CE (95% highest posterior density (HPD), 1607–1749). The GII Pro region emerged around 1752 CE (95%HPD, 1707–1794), forming three further lineages. The evolutionary rate of GII Pro region was estimated at more than 10−3 substitutions/site/year. The distribution of the phylogenetic distances of each genotype differed, and showed genetic diversity. Mapping of the negative selection and substitution sites of the Pro structure showed that the substitution sites in the Pro protein were mostly produced under neutral selection in positions structurally adjacent to the active sites for proteolysis, whereas negative selection was observed in residues distant from the active sites. The phylodynamics of GII.P4, GII.P7, GII.P16, GII.P21 and GII.P31 indicated that their effective population sizes increased during the period from 2005 to 2016 and the increase in population size was almost consistent with the collection year of these genotypes. These results suggest that the Pro region of the norovirus GII evolved rapidly, but under no positive selection, with a high genetic divergence, similar to that of the RNA-dependent RNA polymerase (RdRp) region and the VP1 region of noroviruses.